Pengaruh Natrium Alginat Sebagai Polimer Terhadap Karakteristik Fisik Mikropartikel Liofilisat Daun Murbei (Morus alba L.) - Aisyah Fatmawaty; Radhia Riski; Nurul Arfiyanti; Lukman Muslimin (Jurnal Farmasi dan Ilmu Pengobatan, 2017)
The research about the effects of sodium alginate as the polymer to found a stable physical characteristic of microparticles of mulberry leaves (Morus alba L) has been conducted. The purpose of this study was to determine the effect of Na.alginate as the polymer to the physical characteristics of microparticles of M.alba. In this research, the formulation M. alba leaves in the form of microparticles in which the sodium alginate as a polymer with cross connector CaCl2. Microparticles with an ionic gelation method by dispersing mulberry leaf-sodium alginate into a solution of CaCl2. Formula microparticles made with mulberry leaves concentration ratio of sodium alginate (1: 1); (1: 1.5), and (1: 2). Microparticles characterized physically by the size, shape, and appearance by using SEM (scanning electron microscopy), and the adsorption efficiency. The yield on mulberry leaves microparticles obtained are not spherical morphology SEM and entrapment efficiency data cannot be calculated.